2012
DOI: 10.1002/bmc.2822
|View full text |Cite
|
Sign up to set email alerts
|

Simple column‐switching HPLC method for determining levels of the antifungal agent micafungin in human plasma and application to patient samples

Abstract: Micafungin is an echinocandin antifungal agent that is important for treating candidiasis in emergency and intensive care medicine; however, current methods for measuring micafungin plasma levels are lengthy and complicated. We report a simple quantitative method using column-switching high-performance liquid chromatography (HPLC) for determining micafungin in human plasma samples. Human plasma was directly injected into a column-switching HPLC system with a MAYI-ODS pre-column to remove the plasma matrix. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The pairing of these two characteristics allows SEC selection using the semipermeable methoxycellulose coating along with the pores of the porous silica gel particles to effectively exclude unwanted matrix interferences . This MC‐ODS trap has been heavily used in method development and is the focus of a number of application studies .…”
Section: Sps Phase Trap Columnsmentioning
confidence: 99%
“…The pairing of these two characteristics allows SEC selection using the semipermeable methoxycellulose coating along with the pores of the porous silica gel particles to effectively exclude unwanted matrix interferences . This MC‐ODS trap has been heavily used in method development and is the focus of a number of application studies .…”
Section: Sps Phase Trap Columnsmentioning
confidence: 99%
“…Few HPLC methods have been reported in the literature for quantification of Micafungin in plasma [10][11][12][13] . Shengsheng et al reported stability indicating HPLC method for determination of Micafungin and related substances 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Among pretreatment columns, the methylcellulose-immobilized reversed-phase (MC-ODS) column showed excellent performance for drug or chemical analysis of biological samples [1][2][3][4][5][6][7][8] and compounds in the environment. 9 While small molecules, such as drugs and environmental contaminants, enter in and are retained on the reversed-phase inner surface of small pores (12 nm), large molecules, such as proteins are excluded.…”
Section: Introductionmentioning
confidence: 99%